The impact of environmental regulation on Chinese spatial development. Issue 1 (7th July 2019) - Naso, Pedro; Huang, Yi; Swanson, Tim
Abstract: We examine the relationship between environmental regulation and spatial development in China. Exploiting changes in national pollution standards for three industries, ammonia, paper and cement, we measure the impact of environmental regulation on industry productivity. Our results suggest that national pollution standards do not affect industry productivity, but they reallocate productivity spatially. We show that regulated industries located in developing cities increase their productivity compared to similar industries in other cities. This means that environmental regulation affects the spatial distribution of technology in China and might influence long‐term spatial development by reducing geographical disparities.